KANDUNGAN LOGAM BERAT ARSEN PADA ALGA Kappaphycus alvarezii SERTA SEDIMEN DI PERAIRAN DESA BUKU KECAMATAN BELANG KABUPATEN MINAHASA TENGGARA - Laurenzy Tampongangoy; Desy M H Mantiri; Darus SJ Paransa; Rizald M Rompas; James J H Paulus; suzanne Undap (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Kappaphycus alvarezii is one species algae that is very widely developed in the tropical waters, especially in Indonesia. The potential in these waters may decrease due to heavy metal pollution that accumulates in algae and sediments. Analyzing the content of heavy metal arsenic (As), using the SNI 01-2896-1998 test method, namely the metal contamination test method in food. The results obtained from this study were samples of brown and green Kapapphycus alvarezii taken from week I-V detected containing heavy metal arsenic (As) ranging from 0.17 - 0.42 ppm for green algae and 0.12 - 0.37 ppm for brown algae. This As concentration does not exceed the maximum heavy metal limit, which is 1.0 ppm for the maximum limit for heavy metal contamination in food. The concentration of heavy metal in sediments is 1.12 ppm, not exceeding the quality standard in the Environmental Protection Agency (EPA), the maximum heavy metal limit for arsenic in sediment is below 10 mg/kg